What’s gender got to do with it? An assessment of scientific writing on gender studies in Social Sciences and Communication - Morais, Ricardo; Segado-Boj, Francisco; Eloise Fernandes, Clara; Piñeiro-Naval, Valeriano (Revista General de Información y Documentación, 2025)
Gender-related studies have grown in social sciences and communication in the past few years. This interest follows society’s shift and newfound knowledge of gender inequalities. Thus, this research will focus specifically on social sciences and communication, where we question and attempt to evaluate how gender matters have been scrutinised and researched by other authors, also identifying keywords used in the publications, researchers’ collaborations, and their provenience. Our quantitative-method approach tackles the bibliographic information from Web of Science, where we retrieved articles authored by at least one individual affiliated with a Spanish or Portuguese institution, published between 2012 and 2022, and included in the Social Science Citation Index (SSCI) (N = 792) and Emerging Sources Citation Index (ESCI) (N = 489) databases. By adding a filter of the Communication discipline according to the WoS Category, we ended up with a disaggregated sample of 42 articles in SSCI and 39 documents in ESCI. Data reveal that gender studies are developed mainly in social sciences rather than communication, Spanish researchers collaborate more with Anglo-Saxon countries, and social sciences privilege reflections on gender identity and the gender gap. In contrast, communication focuses more on feminism and social media.